Microperimetric Biofeedback Training Improved Visual Acuity after Successful Macular Hole Surgery - Tomoko Ueda-Consolvo; Mitsuya Otsuka; Yumiko Hayashi; Masaaki Ishida; Atsushi Hayashi (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of setting a preferred retinal locus relocation target (PRT) and performing Macular Integrity Assessment (MAIA) biofeedback training in patients showing insufficient recovery of best corrected visual acuity (BCVA) despite successful closure of an idiopathic macular hole (MH). Methods. Retrospective interventional case series. Nine eyes of 9 consecutive patients with the decimal BCVA of less than 0.6 at more than 3 months after successful MH surgery were included. A PRT was chosen based on MAIA microperimetry and the patients underwent MAIA biofeedback training. BCVA, reading speed, fixation stability, and 63% bivariate contour ellipse area (BCEA) were evaluated before and after the training. Statistical analysis was carried out using paired Student’s t-test. Results. PRT was chosen on the nasal side of the closed MH fovea in 8 patients. After the MAIA training, BCVA improved in all patients. The mean logMAR value of BCVA significantly improved from 0.33 to 0.12 (p=0.007). Reading speed improved in all patients (p=0.29), fixation stability improved in 5 patients (p=0.70), and 63% BCEA improved in 7 patients (p=0.21), although these improvements were not statistically significant. Conclusion. MAIA biofeedback training improved visual acuity in patients with insufficient recovery of BCVA after successful MH surgery.